Key Informant Methods: An Innovative Social Mobilization Strategy to enable Communitybased Diagnosis, Treatment and Rehabilitation for People with Disability - Pandey, Ashok; Gautam, Pratima (Journal of Nepal Health Research Council, 2020)
Key informant method is an innovative technique for identifying people who are disabled in the community, by training local volunteers to act as key informants. Key informants are the local native people include teachers, village doctors, local health workers, religious leaders, community leaders, students, traditional healers, police, NGO staffs, health professionals, local journalists, village councils etc. For them, host organization organized a training to train the key informants to identify and refer the suspected disable people. The study proved key informant method as a valid method for identification of disabling children. Key informant method had a high sensitivity (average 98%) for case detection in all groups but specificity was lower (average 44%), particularly for hearing impairment. Key Informant Method can be used to collect data on types of disabilities, cause, the magnitude of impairments, severity, quantify a need for disabled people, and making access to services (including adoption, health check-up, vocational training, rehabilitation, and other facilitation training). Keywords: Bangladesh; disability; key Informant; key informant methods